Cloud Computing Adoption for SMEs - Guan, Yuehui; Khantanapha, Napaporn (เสฏฐวิทย์ปริทัศน์, 2025)
Cloud computing has emerged as a transformative technology for small and medium-sized enterprises (SMEs), enabling them to overcome resource limitations and improve their competitiveness. This paper explores the impact of cloud computing adoption on the core competitiveness of SMEs. SMEs play a crucial role in the global economy by driving job creation, innovation, and economic growth. However, they often face challenges such as limited resources, inadequate management capacity, and fierce market competition, which hinder their development. Cloud computing offers a solution to these challenges by providing scalable, cost-effective IT resources. By adopting cloud technology, SMEs can reduce operational costs, improve efficiency, and enhance their technical capabilities, thereby gaining a competitive edge in the market. The research highlights various cloud computing service models, including Infrastructure as a Service (IaaS), Platform as a Service (PaaS), and Software as a Service (SaaS), which can be tailored to meet the unique needs of SMEs. Moreover, the findings underscore the importance of addressing security concerns to fully leverage the benefits of cloud adoption. The study concludes that cloud computing not only enhances the operational capabilities of SMEs but also contributes to their sustainable development, making it a key driver of competitiveness in the modern business environment.